Analisis Perencanaan Kebutuhan Pupuk Bersubsidi Kelompok Tani Makmur Abadi Kutai Kartanegara - Budiani Fitria Endrawati; Sahid Fajar Pamungkas; Ahmad Jamil (SPECTA Journal of Technology, 2022)
The Makmur Abadi Farmers Group (KTMA) is an organization in the field of oil palm plantations located in Kutai Kartanegara Regency. Problems in planning the availability of subsidized fertilizers interrupt the KTMA plantation activities, such as planning for subsidized fertilizers that have not been planned systematically and often subjective planning of subsidized fertilizers is carried out, so that KTMA has difficulty designing scientific fertilizer needs planning. Based on the calculations, the results of planning using EOQ resulted in ordering 25 sacks of urea fertilizer with 11 orders, reorder point of 254.4 kg, safety stock of 2,040 kg, and TIC of Rp. 2,224,117. Ordered SP-36 fertilizer with EOQ of 23 sacks with 11 orders, reorder point of 254.4 kg, safety stock of 420 kg, and TIC to Rp. 2,169,368. Ordered ZA fertilizer with EOQ of 15 sacks with 12 orders, reorder point of 181.8 kg, safety stock of 1,800 kg, and TIC to Rp. 1,508,527. Ordering NPK fertilizer with EOQ of 50 sacks with 11 orders, reorder point of 512.7 kg, safety stock that can be set at 1,515 kg, and TIC of Rp 4,507,127. Ordering organic fertilizer with EOQ of 30 sacks with 18 orders, reorder point of 512.7 kg, safety stock of 2,295 kg and TIC to Rp 4,019,187.